2021
DOI: 10.3390/ijms22157955
|View full text |Cite
|
Sign up to set email alerts
|

How to Improve the Biocompatibility of Peritoneal Dialysis Solutions (without Jeopardizing the Patient’s Health)

Abstract: Peritoneal dialysis (PD) is an important, if underprescribed, modality for the treatment of patients with end-stage kidney disease. Among the barriers to its wider use are the deleterious effects of currently commercially available glucose-based PD solutions on the morphological integrity and function of the peritoneal membrane due to fibrosis. This is primarily driven by hyperglycaemia due to its effects, through multiple cytokine and transcription factor signalling—and their metabolic sequelae—on the synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 159 publications
0
16
0
Order By: Relevance
“…This was well tolerated and had no effect on peritoneal clearances and residual kidney function. A randomized multicenter clinical trial is currently in progress ( Bonomini et al, 2021 ). It should be appreciated however that although ref ( Bonomini et al, 2021 ; Masola et al, 2021 ; Rago et al, 2021 ) were published in different journals, all were part of MCPI, a publisher of many on-line journals that has been criticized in the past for the quality of its peer review.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…This was well tolerated and had no effect on peritoneal clearances and residual kidney function. A randomized multicenter clinical trial is currently in progress ( Bonomini et al, 2021 ). It should be appreciated however that although ref ( Bonomini et al, 2021 ; Masola et al, 2021 ; Rago et al, 2021 ) were published in different journals, all were part of MCPI, a publisher of many on-line journals that has been criticized in the past for the quality of its peer review.…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…Both solutions demonstrated efficiency in sodium and water removal and have the potential for glucose sparing when used as part of the PD prescription [ 50 ]. A new peritoneal dialysis solution containing L-carnitine and xylitol was recently reported (reviewed in [ 51 ]). These two molecules have molecular weights similar to that of glucose, high water solubility, chemical stability in aqueous solutions, and osmotic properties, which render them suitable for use in PD fluids [ 51 ].…”
Section: Peritoneal Membrane Preservationmentioning
confidence: 99%
“…A new peritoneal dialysis solution containing L-carnitine and xylitol was recently reported (reviewed in [ 51 ]). These two molecules have molecular weights similar to that of glucose, high water solubility, chemical stability in aqueous solutions, and osmotic properties, which render them suitable for use in PD fluids [ 51 ]. Studies on the biocompatibility of a PD solution containing carnitine or xylitol have shown a better profile than glucose-based solutions.…”
Section: Peritoneal Membrane Preservationmentioning
confidence: 99%
“…Finally, promising results may come from the new PD solutions containing L-carnitine and xylitol as osmotic agents [ 43 , 44 , 45 , 46 , 47 ]. Indeed, the use of more biocompatible crystalloid agents [ 43 , 44 , 45 , 46 ] might enable compensated low-sodium PD solutions to be formulated.…”
Section: Alternative Strategies To Remove Sodium By Peritoneal Dialysismentioning
confidence: 99%
“…Finally, promising results may come from the new PD solutions containing L-carnitine and xylitol as osmotic agents [ 43 , 44 , 45 , 46 , 47 ]. Indeed, the use of more biocompatible crystalloid agents [ 43 , 44 , 45 , 46 ] might enable compensated low-sodium PD solutions to be formulated. The initial clinical experience using L-carnitine and xylitol solutions in ten CAPD patients over four consecutive weeks proved safe and well tolerated [ 47 ]; however, larger trials designed ad hoc are needed to verify the efficacy and safety of these new strategies in ESKD patients treated by PD.…”
Section: Alternative Strategies To Remove Sodium By Peritoneal Dialysismentioning
confidence: 99%